2013
DOI: 10.1016/j.it.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the development of cancer immunotherapies

Abstract: Manipulating the immune system in order to induce clinically relevant responses against cancer is a longstanding goal. Interventions to enhance tumor specific immunity through vaccination, sustaining effector T cell activation, or increasing the numbers of tumor specific T cells using ex vivo expansion, have all resulted in clinical successes. Here we examine recent clinical advances and major ongoing studies in the field of cancer immunotherapy. Single agents have so far benefited a limited proportion of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 137 publications
1
36
0
1
Order By: Relevance
“…A 2A R deletion also enhances lymphoma killing and the effectiveness of an anti-lymphoma tumor vaccine (8). Hence, adenosine has been viewed as an inhibitor of T-cell mediated tumor surveillance (9, 10) and blockade of lymphocyte A2ARs has been advocated to facilitate tumor immunotherapy. Curiously, global deletion of A 2A Rs did not affect the growth of B16F10 melanomas or MB49 bladder carcinomas that were not modified by genetic engineering (7, 11), despite the fact that these tumors produce immune cell activation (12).…”
Section: Introductionmentioning
confidence: 99%
“…A 2A R deletion also enhances lymphoma killing and the effectiveness of an anti-lymphoma tumor vaccine (8). Hence, adenosine has been viewed as an inhibitor of T-cell mediated tumor surveillance (9, 10) and blockade of lymphocyte A2ARs has been advocated to facilitate tumor immunotherapy. Curiously, global deletion of A 2A Rs did not affect the growth of B16F10 melanomas or MB49 bladder carcinomas that were not modified by genetic engineering (7, 11), despite the fact that these tumors produce immune cell activation (12).…”
Section: Introductionmentioning
confidence: 99%
“…The biological function of hemocyanins (Hcs) is to transport oxygen throughout the bodies of some invertebrate animals. Recently, Hcs have been of considerable medicinal interest in cancer immunotherapy due to their high immunogenicity [21,22]. In addition, Tchorbanov et al have achieved enhanced antigen immunogenicity for the epitope of influence A virus hemagglutinin bound to RtH or its subunits and they have suggested that Hcs can be successfully used in many immunization protocols as adjuvants or protein carriers [23].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the upregulated expression of TIM-3 on tumorspecific and tumor-infiltrating CD8 C T cells from patients with clear cell (cc)RCC was associated with poor prognosis. 42,43 Since Th1 cells are considered to be effector cells with antitumor activity, achieving a Th1-dominated immune response against RCC cancer cells would be desirable. However, RCC is able to counteract Th1 cell differentiation.…”
Section: Immune Modulation In Rccmentioning
confidence: 99%